The Characteristics of Eye Diseases at Merpati Eye Clinic Dr Kariadi Hospital Semarang in 2020-2022 - Rahmi, Fifin Luthfia; Wildan, Arief; Maharani, Maharani; Prihatningtias, Riski; Nugroho, Trilaksana; Rikiandraswida, Zahira; Ryamizard, Rizal (Diponegoro International Medical Journal, 2023)
Background: The COVID -19 pandemic that has occurred since 2020 has changed and affected all aspects of life. In health services, the pandemic has limited patients from coming to health facilities. Recording of ophthalmology cases in health facilities has an important role in providing information about eye health problems that often occur in the community to identify what are the main challenges faced in the field of eye care.Objective: This study aims to identify the characteristics of eye diseases at the Merpati Eye Polyclinic Dr Kariadi Hospital Semarang in 2020-2022.Methods: This study was a retrospective descriptive study. The clinical characteristic data (gender, age, diagnosis, and Clinic) are retrieved from the medical records of patients suffering from eye diseases who underwent treatment at the Merpati Eye Clinic, Dr. Kariadi Hospital Semarang and was diagnosed in 2020-2022. The data obtained were processed and analyzed using the google sheets program.Results: There were 2961 newly diagnosed patients with the 10 most diagnosed diseases are Refractive disorders (12,87%), Cataracts (11,21%), Glaucoma (10,40%), Diabetic Retinopathy (6,75%), Pseudophakia (5,30%), Papile Atrophy (5,10%), Retinal Vein Occlusion (4,22%), Corneal Ulcer (3,92%), Retinal Detachment (3,71%) and Uveitis (3,51%). Based on age category, the most patients were 51-60 years old (22,29%). Based on gender category, female gender (50,35%) is more than male (49,65%).Conclusion: Of all patients, the 10 most diagnosed diseases were Refractive Disorders, Cataracts, Glaucoma, Diabetic Retinopathy, Pseudophakia, Papillary Atrophy, Retinal Vein Occlusion, Corneal Ulcers, Retinal detachment and Uveitis.